The death of the deal: Are withdrawn acquisition deals informative of CEO quality? - Jacobsen, Stacey (Journal of Financial Economics, 2014)
To examine the market response to positive revelations of chief executive officer (CEO) quality, this study focuses on CEOs who withdraw acquisition bids when the price becomes increasingly expensive. Firms that withdrawal for price-related reasons earn higher withdrawal returns than firms that withdraw for other reasons. This relation is stronger when CEO uncertainty and discretion is high. CEOs unwilling to increase the offer price are less likely to be replaced and more likely to advance to a larger firm than a control group of CEOs. The finding that the market attaches value to CEO-specific information suggests that unobservable manager characteristics can meaningfully impact firm outcomes.